Avaliação da interface python do software de cálculo termodinâmico thermo-calc® para rápida exploração de grandes campos composicionais - Sousa, Vitor (Universidade Federal de São Carlos, 2024)
The multicomponent alloys present an almost unlimited compositional field, and their further development requires the creation of reliable and fast simulation methods that enable researchers to find compositions of interest. One of the most widely used simulation methods currently is the CALPHAD method, which performs phase equilibrium calculations based on modeling of Gibbs free energy, thereby reducing the number of experiments needed to develop new materials. However, with the need to explore increasingly larger compositional fields and to adapt the results to user demands, the Python module of the Thermo-Calc® thermodynamic simulation software was used in a simple problem to assess the difficulty of its usage. As a validation measure, the obtained results were compared with empirical results obtained by the Tsai method.
Evaluation of the Python interface of the thermo-calc® thermodynamic calculation software for rapid exploration of large compositional fields
Keywords: Simulação termodinâmica; Método CALPHAD; Python; Thermo-Calc; Critérios empíricos; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA